2019
DOI: 10.1029/2019tc005545
|View full text |Cite
|
Sign up to set email alerts
|

Thermotectonic History of the Kluane Ranges and Evolution of the Eastern Denali Fault Zone in Southwestern Yukon, Canada

Abstract: Exhumation and landscape evolution along strike‐slip fault systems reflect tectonic processes that accommodate and partition deformation in orogenic settings. We present 17 new apatite (U‐Th)/He (He), zircon He, apatite fission‐track (FT), and zircon FT dates from the eastern Denali fault zone (EDFZ) that bounds the Kluane Ranges in Yukon, Canada. The dates elucidate patterns of deformation along the EDFZ. Mean apatite He, apatite FT, zircon He, and zircon FT sample dates range within ~26–4, ~110–12, ~94–28, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 146 publications
(411 reference statements)
1
20
0
Order By: Relevance
“…FT, (U-Th)/He, and 4 He/ 3 He thermochronometry of basement rocks, sedimentary rocks, and sediments quantify the timing and tempo of erosional and tectonic exhumation in orogens ( Figure 6). In mountain ranges that develop in convergent orogens, these tools lay the foundation to investigate relationships between rapid erosion and surface uplift (e.g., Avdeev & Niemi, 2011;McDermott et al, 2019;Spencer et al, 2019; and many others), propagation of deformation into the foreland (e.g., Gautheron, Espurt, et al, 2013;Lease, Ehlers, & Enkelmann, 2016;Thomson et al, 2017), rapid Quaternary exhumation (Blythe et al, 2007;Shuster et al, 2011;Valla, Rahn, et al, 2016;Yang et al, 2018), and Quaternary climate influences on sediment storage and erosion (e.g., Lang et al, 2018).…”
Section: Tectonicsmentioning
confidence: 99%
“…FT, (U-Th)/He, and 4 He/ 3 He thermochronometry of basement rocks, sedimentary rocks, and sediments quantify the timing and tempo of erosional and tectonic exhumation in orogens ( Figure 6). In mountain ranges that develop in convergent orogens, these tools lay the foundation to investigate relationships between rapid erosion and surface uplift (e.g., Avdeev & Niemi, 2011;McDermott et al, 2019;Spencer et al, 2019; and many others), propagation of deformation into the foreland (e.g., Gautheron, Espurt, et al, 2013;Lease, Ehlers, & Enkelmann, 2016;Thomson et al, 2017), rapid Quaternary exhumation (Blythe et al, 2007;Shuster et al, 2011;Valla, Rahn, et al, 2016;Yang et al, 2018), and Quaternary climate influences on sediment storage and erosion (e.g., Lang et al, 2018).…”
Section: Tectonicsmentioning
confidence: 99%
“…Ca. 30-20 Ma (Figure 12c): The Oligocene and Early Miocene marks a major change in the geology of southern Alaska and southwestern Yukon, which involves the onset of exhumation in the Alaska Range and the Kluane Ranges (Benowitz et al, , 2012(Benowitz et al, , 2014Lease et al, 2016;McDermott et al, 2019), drainage reorganization (Benowitz et al, 2019;Brennan & Ridgway, 2015;Finzel et al, 2011Finzel et al, , 2015, onset of Wrangell volcanism (Berkelhammer et al, 2019;Brueseke et al, 2019), and development of the St. Elias fold-andthrust belt (Bruhn et al, 2004;Pavlis et al, 2012). Contemporaneous events in our study area include the post-32 Ma reactivation of the Valdez Creek shear zone indicated by cooling ages and brittle deformation features, development of an imbricate thrust system along the southern flank of the eastern Alaska Range (Valdez Creek, Broxson Gulch, Airstrip, and Rainy Creek faults), and retrograde metamorphism of the Maclaren schist (Waldien et al, 2021).…”
Section: Ca 33 Ma (Figurementioning
confidence: 99%
“…It is important to emphasize that the tabulated separation estimates consider only the active strand of the Denali fault. We recognize the likelihood of an older Denali fault system, which may have had multiple strands active during the Cretaceous (McDermott et al, 2019;Miller et al, 2002;Wahrhaftig et al, 1975). Herein, our use of the words Denali fault refers to the active strand of the fault, which appears to have been a single highly localized strand for much of the Cenozoic (Cole et al, 1999;Regan et al, 2021).…”
Section: Slip On the Modern Denali Faultmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing radiation damage in zircon manifests visually as increasing crystal discoloration and opacity (Holland & Gottfried, 1955;Nasdala et al, 1995Nasdala et al, , 2001Woodhead et al, 1991). Selecting grains that represent the range of visual metamictization has been demonstrated to yield a >1,000 ppm eU range within zircons from a single sample Flowers et al, 2020;McDermott et al, 2019). Studies that applied this visual metamictization approach were able to characterize the relationship(s) between date and eU, and thus the low-temperature thermal histories, from their zircon He data that would not have been evident had only the most pristine grains been analyzed Flowers et al, 2020;McDermott et al, 2019).…”
mentioning
confidence: 99%